EVALUASI GAMBAR KERJA DAN DED GEDUNG RSUD TIGARAKSA BERBASIS STANDAR BUKU ARCHITECTURAL DRAFTING AND DESIGN - Iqbal Ghazi Maulana (Universitas Negeri Surabaya, 2025)
Working drawings (construction drawing) play an important role in construction projects as a means of technical communication between planners and executors. Drawings that do not meet proper standards may cause miscommunication in the field and affect the quality of the work. This final project aims to evaluate the conformity of Detailed Engineering Design (DED) and For Construction drawings in the RSUD Tigaraksa project with the standards presented in the book Architectural Drafting and Design, Sixth Edition. The method used is archival research and observation, by reviewing literature and design standards from the book and directly examining the RSUD Tigaraksa working drawings for evaluation. The evaluation was conducted on the site plan, floor plans, roof plans, elevations, sections, and structural drawings. The results indicate deficiencies in several aspects, such as incomplete symbols, unreadable dimensions, and missing technical information. This study is expected to serve as a reference for improving the quality of technical documents in construction projects and supporting more efficient and accurate implementation.